2021
DOI: 10.3390/ijerph18041378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Work and Recreational Physical Activity on Prediabetes Condition among U.S. Adults: NHANES 2015–2016

Abstract: More minutes of physical activity (PA) accumulated during a day are associated with a lower risk of diabetes mellitus type 2. However, it is less known if distinct dimensions of PA can produce a different protective effect in the prevention of prediabetes. The aim of this study was to analyze the impact of work and recreational PA on prediabetes among U.S. adults during the period 2015–2016 using the National Health and Nutrition Examination Survey (NHANES) database. Individuals (n = 4481) with hemoglobin A1c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…In line with this study findings of increased prevalence of obesity and metabolic disturbances among coal miners despite their heavy physical activity, in a recent NHANES study, only increased recreational physical activity was found to be associated with an improved metabolic profile, while occupational physical activity was not ( 84 ). In contrast, in a recent study of Chinese coal miners, the higher level of occupational physical activity was related to a decreased prevalence of metabolic syndrome among them ( 23 ).…”
Section: Discussionsupporting
confidence: 82%
“…In line with this study findings of increased prevalence of obesity and metabolic disturbances among coal miners despite their heavy physical activity, in a recent NHANES study, only increased recreational physical activity was found to be associated with an improved metabolic profile, while occupational physical activity was not ( 84 ). In contrast, in a recent study of Chinese coal miners, the higher level of occupational physical activity was related to a decreased prevalence of metabolic syndrome among them ( 23 ).…”
Section: Discussionsupporting
confidence: 82%
“…The first assumption is that gym users represent an active and health-oriented subset of the general population leading to beneficial adaptations on CV risk factors. Even when compared in terms of age and gender, gyms are frequented by a selected active population, which therefore cares more about health issues, treats risk factors more carefully and generally recognizes a preventive and therapeutic role of PA and exercise [ 31 , 32 ]. The intrinsic role of regularly performed PA that has a strong impact on reducing all CV risk factors should be added to this fact.…”
Section: Discussionmentioning
confidence: 99%
“…Employment is inversely linked to DM in the three waves; studies have found that individuals with DM exit labor earlier, in addition to reducing their quality of work [ 20 ]. Studies suggest that the work environment, type of work and working hours increase the risk of DM [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%